2011
DOI: 10.1111/j.2042-7158.2011.01354.x
|View full text |Cite
|
Sign up to set email alerts
|

Human epithelial carcinoma cytotoxicity and inhibition of DMBA/TPA induced squamous cell carcinoma in Balb/c mice by Acacia catechu heartwood

Abstract: The results suggest that AQCE may exert its chemopreventive activity by acting as an antioxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
(35 reference statements)
0
24
0
Order By: Relevance
“…A. catechu is commonly known as Mimosa catechu , whose phytoconstituents possess several pharmacological properties [15,18,24,25]. A. catechu , a medicinally and economically important plant, may serve as novel source of anti-HIV-1 active compounds.…”
Section: Discussionmentioning
confidence: 99%
“…A. catechu is commonly known as Mimosa catechu , whose phytoconstituents possess several pharmacological properties [15,18,24,25]. A. catechu , a medicinally and economically important plant, may serve as novel source of anti-HIV-1 active compounds.…”
Section: Discussionmentioning
confidence: 99%
“…(Fabaceae) also known as ‘Khadira’ has been extensively used as traditional medicine in India/Asia over a long period of time and a rich source of number of polyphenolic compounds. Previously, we have reported chemopreventive effect of aqueous extract of Acacia catechu in skin and mammary cancer rodent models [5,6]. (+)-Cyanidan-3-ol (CD-3) [3',4',5,7-tetrahydroxyflavan-3-ol] (Figure 1) is the most abundant polyphenolic flavonoid in the Acacia catechu heartwood and studies of the biological effects of CD-3 in cell culture and in vivo models indicated that this compound can inhibit lipid peroxidation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, acetylation of H4K8 can affect gene expression, enhance the maturation of oocytes, improve in vitro fertilization, and induce a specific pattern of acetylation during preimplantation development (Shi et al, 2008). Besides, the acetylation of H3K9 is important for CYP19A1 gene regulation (Monga et al, 2011a), and the latter is the candidate gene encoding aromatase enzyme that catalyses the final rate limiting step in E2 biosynthesis (Conley and Hinshelwood, 2001). Besides, the acetylation of H3K9 is important for CYP19A1 gene regulation (Monga et al, 2011a), and the latter is the candidate gene encoding aromatase enzyme that catalyses the final rate limiting step in E2 biosynthesis (Conley and Hinshelwood, 2001).…”
Section: Discussionmentioning
confidence: 99%